ASSETS PORTFOLIOS OF FINANCIAL USING THE MODEL OF SHARPE AND TREYNOR - Gomero Gonzales, Nicko Alberto (2014)
The stock market has many investment opportunities, with expectations of good results in the end will be translated into sustained and growing performance for the investor , if you choose a good strategy, the risk taken could not compromise the sustainability of structured portfolio. For that purpose, equity finance have a number of models that can make a right choice when demand financial assets; although the degree of predictability there might be a bias between what is observed and what is projected, but not without interest to make decisions in the stock market models. This article, in its first part, methodologically exposes some of these models, such as the Sharpe Ratio, which well could be adjusted to the requirements of those who are used to manage portfolios of financial assets.